Programming for Chemical Engineers Using C, C++, and MATLAB - Kapuno, Raul Raymond (Jones & Bartlett Learning, 2012)
Designed For Chemical Engineering Students And Industry Professionals, Programming For Chemical Engineers Using C, C++, And MATLAB® Shows How To Write Reusable Computer Programs By Guiding The Reader Through The Process Of: Establishing The Theoretical Concept; Determining The Applicable Numerical Methods; Testing The Algorithm Through Manual Calculation; Writing And Debugging The Computer Program Based On The Algorithm; And Validating The Result, Using Statistical Analysis. All Programs In The Book Are Written In The Three Most Popular Languages (C, C++, And MATLAB) Currently Used In The Chemical Engineering Curriculum And In Industry. Because The Book Is Written By A Chemical Engineer, Practitioners And Students Will Learn To Write Programs For Appropriate Subject Matter Of Interest To Them.